A cross-specialty expert opinion on the management of hair loss in gynaecological and endocrinological disorders in Indian patients - Karthikeyan, K.; Anand, N.; Parmar, Girish; Jain, Sandhya (International Journal of Research in Dermatology, 2025)
Hair loss, aggravated by modern social demands and work–life pressures, significantly impacts psychosocial well-being. Disorders affecting both the endocrine and gynaecological systems can induce diverse modifications in the intrinsic mechanisms governing hair growth and its cyclic pattern, resulting in hair loss. Nutritional deficiencies can affect both hair structure and growth in conditions such as telogen effluvium, androgenetic alopecia, female pattern hair loss and alopecia areata. Studies indicate that hormonal imbalances and disruptions in the hair growth cycle may benefit from proper nutritional support. Therefore, the key management strategies include lifestyle modifications, nutritional support and medical interventions such as hormone replacement therapy and topical treatments. Addressing underlying endocrine and nutritional deficiencies is crucial. This consensus provides a comprehensive overview of hair loss disorders associated with endocrine and gynaecological conditions, including hypothyroidism, hyperthyroidism, polycystic ovary syndrome and hair loss occurring during postmenopausal and postpartum periods. It emphasises the importance of a multidisciplinary approach for effective management, involving collaboration between dermatologists, nutritionists, endocrinologists and gynaecologists. This collaborative approach ensures a holistic and effective treatment plan for patients experiencing hair loss, offering a well-rounded perspective on improving patient outcomes.